Analisis Pembagian Harta Warisan dalam Tradisi Adat Minangkabau Ditinjau dari Perspektif Tafsir Al-Azhar - Indri Anjani; Adenan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research analyzes the practice of inheritance distribution within the Minangkabau customary tradition through the perspective of Hamka's Tafsir Al-Azhar, particularly his exegesis of QS. An-Nisa verse 11. The matrilineal Minangkabau inheritance system is often perceived as being at odds with the Qur'anic fara'id provisions, since harta pusaka tinggi (high ancestral property) is inherited through the female line, while the Qur'an regulates proportional shares for both male and female heirs. This study employs a qualitative approach through library research, positioning Tafsir Al-Azhar as the primary data source alongside customary-law and Islamic-inheritance-law literature as secondary data. Data were analyzed through descriptive-analytical content analysis and strengthened through source triangulation. The findings show that Hamka views adat and syariah as reconcilable through a division of legal domains: harta pusaka tinggi is positioned as a collective communal trust that falls outside individual tirkah, while harta pusaka rendah is distributed according to fara'id. A comparison with the classical exegesis of Ibn Kathir shows that the normative certainty of the Nash remains intact as long as harta pusaka tinggi is not treated as an object of individual inheritance. This research offers novelty in the form of a contextual-maqasidi exegetical reading of Minangkabau customary inheritance practice, a topic that has so far been studied predominantly through customary law, sociological, and maslahah mursalah approaches.